Dissemination of Prevention of the Spread of COVID 19 through the 7 Slum Indicators Approach in Cirebon City - Heni Fariatul Aeni; Herlinawati Herlinawati; Lilis Banowati; Suzana Indragiri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Slum areas are known to be incubators of disease because they are occupied by high density residents. This activity aims to conduct dissemination in slum settlements in 11 urban villages (Kesenden, Kebonbaru, Pegambiran, Jagasatru, Pulasaren, Drajat, Sunyaragi, Karyamulya, Argasunya, Harjamukti, and Kecapi) with the theme of Prevention of the spread of COVID-19 through the 7 slum indicators approach. The methods applied in this activity were lecture along with question and answer. This activity was implemented by carrying out health protocols to prevent the transmission of COVID-19 wherein there were only 30 participants attended in each village who were required to wear masks and keep social distancing. This dissemination activity was limited to only 2 hours, effective from 08.30 to 11.00 a.m. Based on the results of the activity implementation, basically most of the people had a fairly good knowledge on COVID-19, but not all had a good attitude since there were some people who thought that the virus mostly attacks the middle to upper class. There was also indifference attitude towards government recommendations since they thought that God determines their health status.